Verifying Larché–Cahn elasticity, a milestone of 20th-century thermodynamics - Shi, Shan (Proc Natl Acad Sci U S A, 2018)
Many materials phenomena are governed by the interaction between chemistry and mechanics. However, it was only in the second half of the 20th century that the theory of open system elasticity by Francis Larché and John W. Cahn concatenated the fields of solid mechanics and alloy chemistry. As the theory’s central materials descriptors, the open system elastic parameters describe how solids deform under stress when solute can rearrange at equilibrium while the chemical potential is held constant. Here, we report experiments verifying the predictions for these parameters. We study the elasticity of nanoporous Pd-H and Pd-Au-H during load cycles imposed by a dynamic mechanical analyzer. Short diffusion paths afford fast equilibration of H in the local strain gradients that carry the macroscopic elastic deformation. The experiment is in excellent agreement with the theory, confirming a central prediction of one of the key contributions to 20th-century thermodynamics.